Inflation preferences - Alexander M. Dietrich; Hassan Afrouzi; Kristian O. R. Myrseth; Raphael Schoenle; Romanos Priftis (Danmarks Nationalbank, 2024)
We document novel survey-based facts about preferred long-run inflation rates among US consumers. Consumers on average prefer a 0.20% annual inflation rate, well below the Federal Reserve's 2% target. Inflation preferences not only correlate with demographic and socioeconomic characteristics, but also with economic reasoning. A randomized control trial reveals that two narratives based on economic models-describing how inflation lowers the real value of wages and money holdings-affect inflation preferences. While our results can inform the design of central bank communication on inflation targets, they also raise questions about the alignment between such targets and consumer preferences.
Keywords: C83; E31; E52; 330; Household expectations; Survey; Inflation preferences